ROS signaling in innate immunity via oxidative protein modifications - Manoharan, Renuka Ramalingam; Prasad, Ankush; Pospíšil, Pavel; Kzhyshkowska, Julia (Frontiers in Immunology, 2024)
The innate immune response represents the first-line of defense against invading pathogens. Reactive oxygen species (ROS) and reactive nitrogen species (RNS) have been implicated in various aspects of innate immune function, which involves respiratory bursts and inflammasome activation. These reactive species widely distributed within the cellular environment are short-lived intermediates that play a vital role in cellular signaling and proliferation and are likely to depend on their subcellular site of formation. NADPH oxidase complex of phagocytes is known to generate superoxide anion radical that functions as a precursor for antimicrobial hydrogen peroxide (H2O2) production, and H2O2 is utilized by myeloperoxidase (MPO) to generate hypochlorous acid (HOCl) that mediates pathogen killing. H2O2 modulates the expression of redox-responsive transcriptional factors, namely NF-kB, NRF2, and HIF-1, thereby mediating redox-based epigenetic modification. Survival and function of immune cells are under redox control and depend on intracellular and extracellular levels of ROS/RNS. The current review focuses on redox factors involved in the activation of immune response and the role of ROS in oxidative modification of proteins in macrophage polarization and neutrophil function.